Abatacept retention and clinical outcomes in Austrian patients with rheumatoid arthritis: real-world data from the 2-year ACTION study - Peichl, Peter; Alten, Rieke; Galeazzi, Mauro; Lorenz, Hanns-Martin; Nüsslein, Hubert; Navarro, Federico; Elbez, Yedid; Chartier, Melanie; Hackl, Roland; Rauch, Christiane; Connolly, Sean E. (Wiener Medizinische Wochenschrift, 2019)
Background AbataCepT In rOutiNe clinical practice (ACTION; NCT02109666) was a 2-year international observational study of patients with moderate to severe rheumatoid arthritis. Methods Baseline characteristics, abatacept retention rates, and clinical outcomes were compared by treatment line in the Austrian cohort of ACTION. Results Of 100 patients enrolled in Austria, 98 (98.0%) were evaluable: 33/98 (33.7%) biologic naive and 65/98 (66.3%) with >= 1 prior biologic failure. At baseline, biologic-naive patients had shorter disease duration and lower concomitant corticosteroid use than biologic-failure patients. Overall crude abatacept retention rate was 60.5% and retention rate was higher in biologic-naive (65.1%) versus biologic-failure (58.0%) patients. Good/moderate EULAR (European League Against Rheumatism) response rates were 85.7% in biologic-naive and 100% in biologic-failure patients. Conclusions In the Austrian cohort of ACTION, overall abatacept retention at 2 years was high, with higher retention rates in patients receiving abatacept as an earlier treatment line. Good/moderate EULAR response rate was higher in biologic-failure than in biologic-naive patients.
CRIS-Team WoS Importer:2019-11-08

Abatacept retention and clinical outcomes in rheumatoid arthritis: real-world data from the German cohort of the ACTION study and a comparison with other participating countries - Alten, Rieke; Feist, Eugen; Lorenz, Hanns Martin; Nüsslein, Hubert; Voll, Reinhard E.; Chartier, Melanie; Elbez, Yedid; Rauch, Christiane (Clinical Rheumatology, 2019)
Introduction: AbataCepT In rOutiNe clinical practice (ACTION; NCT02109666) was an observational study of patients with rheumatoid arthritis who initiated intravenous abatacept in clinical practice. We aimed to compare abatacept retention rates and clinical outcomes in patients from Germany versus other countries. Method: Baseline characteristics, crude retention rates, and clinical outcomes were compared by treatment line in the German cohort at 2 years. In addition, biologic-naïve patients were compared with biologic-naïve patients pooled from other participating countries. Results: In the German cohort, 677/680 (99.6%) patients enrolled were evaluable and 171/677 (25.3%) were biologic naïve. At baseline, abatacept monotherapy was received by a similar proportion of biologic-naïve and biologic-failure patients in the German cohort, but by a greater proportion of biologic-naïve patients in German versus other countries cohort (27.5 vs. 12.9%). The overall crude abatacept retention rate at 2 years in the German cohort was 39.9%; retention rate did not differ significantly by treatment line, but among biologic-naïve patients it was lower in Germany than in the other countries cohort (42.1 vs. 58.7%; log-rank test p < 0.001). At 2 years, good/moderate European League Against Rheumatism (EULAR) response rates in biologic-naïve patients were 85.5% in the German and 92.1% in other countries cohort (p = 0.163). Conclusions: In the German cohort of ACTION, abatacept retention at 2 years was similar in biologic-naïve and biologic-failure patients. Biologic-naïve patients in German cohort had a significantly lower abatacept retention rate and a trend of lower good/moderate EULAR response rate than those in the other countries cohort. Key Points: • Analyses of data from national patient cohorts provide insight on local treatment patterns. • In the German cohort of the ACTION study, abatacept retention at 2 years was similar in biologic-naïve and biologic-failure patients. • Biologic-naïve patients from the German cohort had a significantly lower abatacept retention rate and a trend of lower good/moderate EULAR response rate than patients from other countries. • Data from large international studies may not be directly applicable to individual countries.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Biologic-failure patients; Biologic-naïve patients; Clinical practice; Germany; Rheumatoid arthritis

ANTI-MODIFIED PROTEIN ANTIBODY RESPONSE PATTERN INFLUENCES THE RISK FOR DISEASE RELAPSE IN RHEUMATOID ARTHRITIS PATIENTS TAPERING DISEASE MODIFYING ANTI-RHEUMATIC DRUGS - Figueiredo, C.; Bang, H.; Cobra, J. F.; Englbrecht, Matthias; Hueber, A. J.; Haschka, J.; Manger, Bernhard; Kleyer, A.; Reiser, M.; Finzel, S.; Tony, H-P.; Kleinert, S.; et al. (2016)
EVALuna2:13494

Correction to: Predictors of abatacept retention over 2 years in patients with rheumatoid arthritis: results from the real-world ACTION study (Clinical Rheumatology, (2019), 38, 5, (1413-1424), 10.1007/s10067-019-04449-w) - Alten, Rieke; Mariette, Xavier; Lorenz, Hanns Martin; Nüsslein, Hubert; Galeazzi, Mauro; Navarro, Federico; Chartier, Melanie; Heitzmann, Julia; Poncet, Coralie; Rauch, Christiane; Le Bars, Manuela (Clinical Rheumatology, 2019)
The article listed above was initially published with incorrect copyright information. Upon publication of this Correction, the copyright of this article changed to “The Author(s)”. The original article has been corrected. Publisher’s note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.
CRIS-Team Scopus Importer:2019-05-28

Cost-effective tapering algorithm in patients with rheumatoid arthritis: Combination of multibiomarker disease activity score and autoantibody status - Hagen, Melanie; Englbrecht, Matthias; Haschka, Judith; Reiser, Michaela; Kleyer, Arnd; Hueber, Axel; Manger, Bernhard; Figueiredo, Camille; Cobra, Jayme Fogagnolo; Tony, Hans-Peter; Finzel, Stephanie; Kleinert, Stefan; et al. (Journal of Rheumatology, 2019)
Objective. To analyze the effect of a risk-stratified disease-modifying antirheumatic drug (DMARD)- tapering algorithm based on multibiomarker disease activity (MBDA) score and anticitrullinated protein antibodies (ACPA) on direct treatment costs for patients with rheumatoid arthritis (RA) in sustained remission. Methods. The study was a posthoc retrospective analysis of direct treatment costs for 146 patients with RA in sustained remission tapering and stopping DMARD treatment, in the prospective randomized RETRO study. MBDA scores and ACPA status were determined in baseline samples of patients continuing DMARD (arm 1), tapering their dose by 50% (arm 2), or stopping after tapering (arm 3). Patients were followed over 1 year, and direct treatment costs were evaluated every 3 months. MBDA and ACPA status were used as predictors creating a risk-stratified tapering algorithm based on relapse rates. Results. RA patients with a low MBDA score (< 30 units) and negative ACPA showed the lowest relapse risk (19%), while double-positive patients showed high relapse risk (61%). In ACPA-negative and MBDA-negative (< 30 units), and ACPA or MBDA single-positive (> 30 units) groups, DMARD tapering appears feasible. Considering only patients without flare, direct costs for synthetic and biologic DMARD in the ACPA/MBDA-negative and single positive groups (n = 41) would have been ϵ372,245.16 for full-dose treatment over 1 year. Tapering and stopping DMARD in this low-risk relapse group allowed a reduction of ϵ219,712.03 of DMARD costs. Average reduction of DMARD costs per patient was ϵ5358.83. Conclusion. Combining MBDA score and ACPA status at baseline may allow risk stratification for successful DMARD tapering and cost-effective use of biologic DMARD in patients in deep remission as defined by the 28-joint count Disease Activity Score using erythrocyte sedimentation rate.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Anticyclic Citrullinated Protein Antibodies; Drug Costs; Multibiomarker Disease Activity; Remission; Rheumatoid Arthritis; Tapering

Effectiveness and safety of anti-tumour necrosis factor therapy with certolizumab pegol observed in real-life rheumatoid arthritis patients in Germany: results from the non-interventional FαsT study - Burmester, Gerd; Nüsslein, Hubert; von Hinüber, Ulrich; Detert, Jacqueline; Richter, Constanze; Kumke, Thomas; Leunikava, Iryna; Lendl, Udo; Fricke, Dieter; Müller-Ladner, Ulf (Clinical and Experimental Rheumatology, 2019)
OBJECTIVES: To report the tolerability and effectiveness of certolizumab pegol (CZP) for the treatment of patients with active rheumatoid arthritis (RA) in a routine clinical practice setting. METHODS: FαsT (NCT01069419) was a non-interventional, observational 104-week (wk) study performed at 163 sites in Germany. RA patients were treated according to the treating physician's discretion. Clinical remission (DAS28-CRP<2.6) at wk 104 was the primary endpoint of the study. Remission data based on ESR (DAS28-ESR<2.6) were also assessed. Secondary endpoints included the effect of CZP treatment on pain, physical function and disease activity. Safety data were collected at all study visits. RESULTS: 1,117 patients were enrolled in the FαsT study (78% female, mean age: 55 years). Rapid responses were observed at wk 6 (18.7% and 12.9% patients in DAS28-CRP and DAS28-ESR remission, respectively) with improvements sustained over 2 years (20.0% and 13.9% patients achieved DAS28-CRP and DAS28-ESR remission, respectively at wk 104). Anti-TNF naïve patients exhibited greater improvements than anti-TNF experienced patients (mean DAS28-ESR change from baseline [CfB] -1.3, -1.5 and -1.7 for patients with ≥2, 1 and no anti-TNFs, respectively at wk104). Improvements were reported in all secondary endpoint measures. 1,111 patients were exposed to CZP for a total of 1,538 patient-years during the study. 2,000 treatment-emergent adverse events (TEAEs) were reported in 745 patients (67.1%); 9 (0.8%) experienced TEAEs with fatal outcome. CONCLUSIONS: CZP demonstrated efficacy and safety outcomes reflective of those observed in trial settings. Rapid reductions in disease activity and improvements in physical function were maintained up to wk 104.
CRIS-Team Scopus Importer:2019-09-27

ELEVATED MULTI-BIOMARKER DISEASE ACTIVITY (MBDA) PREDICTS RELAPSES IN RA PATIENTS IN SUSTAINED REMISSION TAPERING TUMOUR NECROSIS FACTOR INHIBITOR THERAPY-RESULTS FROM THE RANDOMIZED CONTROLLED RETRO STUDY - Rech, Jürgen; Hagen, M.; Englbrecht, M.; Haschka, J.; Reiser, M.; Kleyer, A.; Hueber, A.; Manger, Bernhard; Figuereido, C.; Cobra, J. Fogagnolo; Tony, H-P.; Finzel, S.; et al. (2017)
EVALuna2:34452

FACTORS ASSOCIATED WITH PERSISTENT DRUG-FREE REMISSION IN PATIENTS WITH RHEUMATOID ARTHRITIS - Valor, Larissa; Hagen, Melanie; Reiser, Michaela; Kleyer, Arnd; Hartmann, Fabian; Manger, Bernhard; Schett, Georg; Rech, Jürgen; Tascilar, Koray; Haschka, J.; Englbrecht, Matthias; Hueber, Axel; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-16

MULTI-BIOMARKER DISEASE ACTIVITY AND AUTOANTIBODY STATUS LEAD TO COST EFFECTIVE TAPERING ALGORITHMS IN RHEUMATOID ARTHRITIS PATIENTS IN SUSTAINED REMISSION - Hagen, Melanie; Englbrecht, Matthias; Haschka, J.; Reiser, M.; Kleyer, Arnd; Hueber, A.; Manger, Bernhard; Figuereido, C.; Cobra, J. Fogagnolo; Tony, H. -P.; Finzel, S.; Kleinert, S.; et al. (2017)
EVALuna2:34451

Prediction of Disease Relapses By Multi-Biomarker Disease Test Activity in Rheumatoid Arthritis Patients Tapering DMARD Treatment - Rech, Jürgen; Hueber, Axel; Englbrecht, Matthias; Finzel, Stephanie; Haschka, Judith; Manger, Bernhard; Kleyer, Arnd; Reiser, Michaela; Tony, Hans-Peter; Kleinert, Stefan; Feuchtenberger, Martin; Fleck, Martin; et al. (2015)
EVALuna2:13331

Predictors of abatacept retention over 2 years in patients with rheumatoid arthritis: results from the real-world ACTION study - Alten, Rieke; Mariette, Xavier; Lorenz, Hanns Martin; Nüsslein, Hubert; Galeazzi, Mauro; Navarro, Federico; Chartier, Melanie; Heitzmann, Julia; Poncet, Coralie; Rauch, Christiane; Le Bars, Manuela (Clinical Rheumatology, 2019)
Objectives: Evaluate abatacept retention over 2 years in the AbataCepT In rOutiNe clinical practice (ACTION) study. Method: ACTION was an international, observational study of patients with moderate-to-severe rheumatoid arthritis (RA) who initiated intravenous abatacept. Crude abatacept retention rates over 2 years were estimated using Kaplan–Meier analyses in biologic-naive and -failure patients. Clinically relevant risk factors and significant prognostic factors for retention were evaluated using a Cox proportional hazards multivariable model. Results: Overall, 2350/2364 enrolled patients were evaluable; 673 (28.6%) were biologic naive and 1677 (71.4%) had prior biologic failure (1 biologic, 728/1677 [43.4%]; ≥ 2 biologics, 949/1677 [56.6%]). Abatacept retention rate (95% confidence interval [CI]) at 2 years was 47.9% (45.7, 50.0): 54.5% (50.4, 58.3) for biologic-naive vs 45.2% (42.7, 47.7) for biologic-failure patients (log-rank P < 0.001). For patients with 1 and ≥ 2 prior biologic failures, respectively, retention rates (95% CI) were 50.2% (46.3, 53.9) vs 41.3% (38.0, 44.6; log-rank P < 0.001). Main reasons for discontinuation (biologic-naive vs biologic-failure, respectively) were lack of efficacy (61.4 vs 67.7%) and safety (21.3 vs 21.2%). Rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) double positivity versus negativity were predictive of higher retention in both biologic-naive (hazard ratio [HR] [95% CI] 0.71 [0.53, 0.96]; P = 0.019) and biologic-failure patients (HR [95% CI] 0.76 [0.62, 0.94]; P = 0.035). Conclusions: Abatacept initiation as earlier vs later line of therapy in RA may achieve higher 2-year retention rates. RF and anti-CCP seropositivity could predict increased abatacept retention, irrespective of treatment line. Trial registration: NCT02109666.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Biologic; Efficacy; Predictor; Remission; Rheumatoid arthritis

RETRO - STUDY OF REDUCTION OF THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS IN ONGOING REMISSION - Haschka, J.; Englbrecht, Matthias; Hueber, Axel; Manger, Bernhard; Kleyer, Arnd; Reiser, M.; Finzel, Stephanie; Tony, H. -P.; Kleinert, S.; Feuchtenberger, M.; Fleck, M.; Manger, Karin; et al. (2015)
EVALuna2:34460

Risk of infections in rheumatoid arthritis patients treated with tocilizumab - Lang, Veronika R.; Englbrecht, Matthias; Rech, Jürgen; Nüsslein, Hubert; Manger, Karin; Schuch, Florian; Tony, Hans-Peter; Fleck, Martin; Manger, Bernhard; Schett, Georg; Zwerina, Jochen (Rheumatology, 2012)
Objectives: To investigate the occurrence and risk factors for infections in RA patients treated with tocilizumab. Methods: A cohort of all RA patients (n = 112) starting tocilizumab therapy between October 2008 and March 2010 in Northern Bavaria was screened for infections. Mild/moderate and severe infections were recorded. Multivariate logistic regression analysis was used to define risk factors for infection. Results: Overall, 26 patients developed infections [23.2%; 58.0/100 patient-years (py)], 18 of them were mild to moderate (16.1%, 40.1/100 py) and 8 were severe (17.9/100 py). Concomitant use of LEF and prednisone, high disease activity and previous therapy with rituximab were associated with the occurrence of mild/moderate infections. Severe infections were related to longer disease duration, exposure to more than three previous DMARDs and concomitant therapy with proton-pump inhibitors. Conclusion: The rate of infection in RA patients treated with tocilizumab in clinical practice is higher than in the clinical trial populations. Increased attention should especially be given to patients with longer disease duration, previous exposure to multiple DMARDs, i.e. previous exposure to rituximab and those receiving concomitant LEF, prednisone or proton-pump inhibitor treatment. © The Author 2011. Published by Oxford University Press on behalf of the British Society for Rheumatology. All rights reserved.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Infections; Rheumatoid arthritis; Tocilizumab